PENGARUH OPINI AUDIT TERHADAP PENGUNGKAPAN LAPORAN KEUANGAN KEMENTERIAN/LEMBAGA PEMERINTAH DI INDONESIA - Martha Carolina (Pusat Kajian Anggaran, 2019)
Disclosure is the most important aspect in financial statement. Full disclosure provides an easy understanding about the contents for user in order to make precise decision. This research examines full disclosure of Ministries/Insitutions in Indonesia based on Governmental Accounting Standard (SAP). The study was conducted to analyze the effect of audit opinions on the level disclosures of Ministries/Insitutions. The model using the lag effect, which examines the influence of audit opinions 2016 on the disclosures of financial statement in 2017. The result showed opinion has a positive and significant impact on disclosure.